PERTANGGUNG JAWABAN HUKUM TERHADAP ANAK SEBAGAI KORBAN CYBERBULLYING PADA MEDIA SOSIAL - Panjaitan, Ranto Daniel; Zukriadi, Diki (LPPM Universitas Putera Batam, 2024)
Social media has now become an inseparable need for human life, not only for adults and teenagers but hasspread to all levels, including young children. However, quite a few social media users misuse its benefits, oneof which is using social media for bullying or cyberbullying. Cyberbullying carried out by children under 12 yearsof age experiences a legal vacuum because responsibility towards the victim is deemed not to be in accordancewith the existing legal basis. The aim of this research is to find out how legal protection is for victims of childbullying in Indonesia and what legal accountability is for perpetrators of bullying who are children, usingnormative juridical research methods and analyzed using qualitative analysis methods. The results of theresearch are that in Indonesia cyberbullying is regulated in several regulations such as in the Criminal Codewhich is stated in article 310 paragraph (1) in the form of cyber harassment. Apart from that, cyberbullying isalso regulated in Law number 8 of 2008 concerning Information and Electronic Transactions, regulated inarticles 27 to article 29. Children as victims must be specially protected by the government and relatedinstitutions as regulated in Law number 35 of 2014 regarding changes to Law number 23 of 2002 concerningchild protection.